The Role of Artificial Intelligence in Enhancing IT Governance in Saudi Arabia: Opportunities, Challenges, and Future Directions - Fatma Abudaqqa (European Scientific Journal, ESJ, 2025)
Saudi Arabia’s Vision 2030 aims to transform the Kingdom into a knowledge-based economy by promoting technological innovation and increasing transparency in public administration. In support of this vision, the National Strategy for Data and Artificial Intelligence (AI), led by the Saudi Data and AI Authority (SDAIA), seeks to position Saudi Arabia as a global leader in AI by 2030. This study explores the potential of AI to enhance IT governance within the Saudi context. Drawing on established theoretical frameworks and a structured research methodology, the paper reviews AI adoption across key sectors to contextualize its current trajectory. The analysis highlights areas where AI can improve governance mechanisms and identifies key barriers to implementation, including institutional, technical, and regulatory challenges. The study concludes with strategic recommendations to guide policymakers and practitioners in leveraging AI to strengthen IT governance across the Kingdom.